Porphyry in fragments reception of an anti-Christian text in late antiquity - Magny, Ariane (Farnham Ashgate, 2014)
The Greek philosopher Porphyry of Tyre had a reputation as the fiercest critic of Christianity. It was well-deserved: he composed (at the end the 3rd c. A.D.) fifteen discourses against the Christians, so offensive that Christian emperors ordered them to be burnt. We thus rely on the testimonies of three prominent Christian writers to know what Porphyry wrote. Scholars have long thought that we could rely on those testimonies to know Porphyry's ideas. Exploring early religious debates which still resonate today, 'Porphyry in Fragments' argues instead that Porphyry's actual thoughts became mixed with the thoughts of the Christians who preserved his ideas, as well as those of other Christian opponents.0
Includes bibliographical references and index.
Keywords: Porphyry, -- approximately 234-approximately 305.; Eusebius, -- of Caesarea, Bishop of Caesarea, -- approximately 260-approximately 340.; Jerome, -- Saint, -- -419 or 420.; Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- of Hippo, Saint, -- 354-430.; 1 <38> PORPHYRIUS -- Griekse filosofie--PORPHYRIUS